1975
DOI: 10.1080/00223980.1975.9915793
|View full text |Cite
|
Sign up to set email alerts
|

Problem-Solving Training Groups for Hospitalized Psychiatric Patients

Abstract: Small groups lasting eight sessions each and aimed at improving patient's interpersonal problem-solving skills were conducted for a total of 41 hospitalized psychiatric patients. Forty control patients received the same pre and posttests but notraining. Twenty-three patients participated in play-reading groups without problem-solving training (placebo condition). Three separate 3 by 2 repeated measures analyses of variance showed that hospitalization alone improved the patient's functioning on the criterion te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…Thus, the findings are not attributable to differences in verbosity. These data also provide some ancillary support for research that has Downloaded by [University of New Hampshire] at 15:01 08 February 2015 found problem-solving deficits among chronic psychiatric patients (e.g., Bellack et al, 1989;Coche & Douglas, 1977;Coche & Flick, 1975;Hansen et al, 1985;Platt & Spivack, 1972a, 1972b. Findings from Study 2 ad~d to this growing body of literature.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Thus, the findings are not attributable to differences in verbosity. These data also provide some ancillary support for research that has Downloaded by [University of New Hampshire] at 15:01 08 February 2015 found problem-solving deficits among chronic psychiatric patients (e.g., Bellack et al, 1989;Coche & Douglas, 1977;Coche & Flick, 1975;Hansen et al, 1985;Platt & Spivack, 1972a, 1972b. Findings from Study 2 ad~d to this growing body of literature.…”
Section: Discussionsupporting
confidence: 67%
“…Study 2 addressed some of these methodological concerns by comparing the PPSS scores of a chronic psychiatric group with a nonpsychiatric group. Although there is considerable controversy regarding the cause of personal problem-solving deficits in chronic psychiatric populations (e.g., Bellack, Morrison, & Mueser, 1989), several studies have documented such deficiencies (e.g., Coche & Douglas, 1977;Coche & Flick, 1975;Hansen, St. Lawrence, & Christoff, 1985;Platt & Spivack, 1972a, 1972b. Therefore the psychiatric group, compared with the nonpsychiatric group, was expected to report more psychiatric symptoms, a greater number of current problems, and less effective personal problem-solving skills as measured by the PPSS.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have found problem-solving training effective in enhancing the interactions of adult psychiatric patients (Coché and Douglas, 1977;Coché and Flick 1975;Edelstein et al, 1980;Hansen et al, 1985). In most of these studies skill training was shown to have generalized outside practice sessions and in some cases (such as the work of Hansen et al and that of Edelstein et al) training gains were maintained after modest follow-up intervals of four months.…”
Section: Intervention Studiesmentioning
confidence: 99%
“…Other carefully conducted ICPS/SPS interventions that have had significant behavioral impact on older populations include some with normal elementary school age children (Elardo & Caldwell, 1979;Elias, 1980;Mannarino, Christy, Durlak, & Magnussen, 1982), and some in populations with special needs: in hyperactive 7-year-olds (Camp & Bash, 1978, 1981, in educable-retarded 6-to 12-year-olds (Healey, 1977), in emotionally disturbed fifth graders (Natov, 1981), in learning-disabled 8-to 12-year-olds (Weiner, 1978), in young adult alcoholics (Intagliata, 1978), and in short-term young adult inpatients (Coch6 & Flick, 1975). 4 We are encouraged to learn that ICPS/SPS intervention has helped to reduce the intensity of stressors experienced at transition to middle school (Grade 6) and that the amount of stress experienced directly relates to the length of training (Elias, 1984).…”
Section: George Spivack 2 and Myrna B Shurementioning
confidence: 99%